Hidden value how great companies achieve extraordinary results with ordinary people - O'Reilly, Charles A. (Boston Harvard Business School Press, 2000)
Discover how the best companies win not by acquiring the right people - but by building the right organization. The 'war for talent' is one battle every company believes it should be waging. But while competitors are busy chasing after the same 'hot' individuals, smart companies are doing something infinitely more useful and far more difficult to copy - they're building organizations that make it possible for ordinary people at every desk and cubicle in their companies to perform as if they were stars. Blowing up the prevailing wisdom that companies must chase and acquire top talent in order to remain successful, "Hidden Value" argues instead that the source of sustained competitive advantage already exists within every organization. O'Reilly and Pfeffer, leading experts on organizational behavior and human resources, argue that how a firm creates and uses talent is far more important than how the firm attracts talent. The authors provide vivid, detailed case studies of several organizations in widely disparate industries - including Southwest Airlines, Cisco Systems, The Men's Wearhouse, and NUMMI - to illustrate how long-term success comes from value-driven, interrelated systems that align good people management with corporate strategy. In a refreshing break from management tomes that force-feed superficial frameworks and trite 'rules', the authors instead allow the company stories to take center stage. They guide readers in discovering for themselves how seven different firms maximize talent, why one firm hasn't fully released the hidden value in its work force, and, most importantly, how the winning companies have made it tough for competitors to imitate them. Collectively, the stories reveal a common path to success that places values before strategy, emphasizes implementation over planning, and focuses on getting the best out of all employees, not just individual stars. The authors also explore concerns or questions managers might have about how each company's experience parallels or conflicts with their own. Providing a rare opportunity for managers to actively participate in an invaluable learning process, "Hidden Value" offers a customizable template for building high-performance, people-centered organizations.
Includes bibliographical references and index.
Keywords: Industrial management--United States--Case studies